2007
DOI: 10.1111/j.1365-294x.2007.03479.x
|View full text |Cite
|
Sign up to set email alerts
|

Non‐gradual variation in colour morphs of the strawberry poison frog Dendrobates pumilio: genetic and geographical isolation suggest a role for selection in maintaining polymorphism

Abstract: The relative roles that geographical isolation and selection play in driving population divergence remain one of the central questions in evolutionary biology. We approached this question by investigating genetic and morphological variation among populations of the strawberry poison frog, Dendrobates pumilio, in the Bocas del Toro archipelago, Panama. We found significant population genetic structure and isolation by distance based on amplified fragment length polymorphism markers. Snout vent length (SVL), col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
90
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(98 citation statements)
references
References 43 publications
7
90
0
1
Order By: Relevance
“…One counterargument to the hypothesis that decreased predation pressure would permit the observed higher warning signal diversity in O. pumilio is that other dendrobatids present on the islands do not show the same level of diversity in their warning signal (Summers et al 2003;Rudh et al 2007). A genetic pre-disposition toward phenotypic variability (including warning signal diversity) in O. pumilio, though, may be at least one explanation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One counterargument to the hypothesis that decreased predation pressure would permit the observed higher warning signal diversity in O. pumilio is that other dendrobatids present on the islands do not show the same level of diversity in their warning signal (Summers et al 2003;Rudh et al 2007). A genetic pre-disposition toward phenotypic variability (including warning signal diversity) in O. pumilio, though, may be at least one explanation.…”
Section: Discussionmentioning
confidence: 99%
“…1), O. pumilio displays a high level of warning signal diversity. This diversity manifests itself in color polytypism across the archipelago and polymorphism in some contact zones and on some islands, most notably on Isla Bastimentos (see plates in Myers and Daly 1983;Rudh et al 2007;Saporito et al 2007a). Over 15 color morphs are present in the archipelago and include disparate colors such as yellow, red, blue, lime green, and bronze among others, with different morphs occurring at times on the same island (Siddiqi et al 2004).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Amplified fragment length polymorphisms (AFLPs) have been shown to provide phylogenetic resolution among recently and rapidly radiating groups in which sequence data have failed (17)(18)(19)(20)(21)(22). The increased resolution of AFLPs is associated with their nuclear genome-wide distribution, which overcomes problems associated with locus-specific effects, and the large number of polymorphisms that can be easily characterized.…”
mentioning
confidence: 99%
“…Host preference may allow insects to feed more effectively on the host plants, which in turn results in restriction of gene flow between populations and promotes host race formation of the feeding insects (Magalhães et al, 2007). Studies have also suggested that morphological divergence between populations is a result of widespread reproductive isolation and local adaptation (Sota et al, 2007) and may be a starting point of a speciation process (Rudh et al, 2007).…”
Section: Introductionmentioning
confidence: 99%